Study of knowledge and attitude among college-going students toward voluntary blood donation from north India - Mishra, Shailesh Kumar (J Blood Med, 2016)
INTRODUCTION: The study was conducted to assess the knowledge and attitude of college-going students toward voluntary blood donation and to bring out and compare the reasons for donating or not donating blood. MATERIALS AND METHODS: This cross-sectional study was conducted on 1,000 college-going students after taking their consent for participation using a prevalidated, self-administered, structured questionnaire after its content and construct validation. RESULTS: The difference in the means of the level of knowledge among the donor (mean: 14.71±2.48) and nondonor students (mean: 11.55±2.82) was statistically significant. There was significant impact of previous blood donation on the level of knowledge in donor students. The attitude toward blood donation was more positive among blood donor as compared to nondonor students, and the difference in their means was statistically significant. About one in two (45.8%) college-going students fear that either they are not fit enough to donate blood (26.8%) or that they will become weak (19%) after blood donation. Almost one in four (27.4%) have fear of needle pain; therefore, they do not come forward for blood donation. INTERPRETATION AND CONCLUSION: The most significant reason hindering blood donation comes out to be related to health of the individual donor. The findings of this study conclude that the national targets of voluntary blood donation could be better met with specific blood donor information, education, motivation, and recruitment strategies focusing on the myths and misconceptions prevalent in the donor demographic area of that particular region, specifically targeting high-school children in countries developing a volunteer donor base.